An inter-disciplinary study of how democracies eventually emulate authoritarian regimes, considering 1984 as a forewarning - Hassan, Md. Hasibul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.